Effects of Aquatic Exercise Programs on Health-Promoting Lifestyle and Psychological Distress in Children With Developmental Disorders A Narrative Review - Ahmadi , Eskandar; Naderinasab, Mahdi; Hosseini, Seyed sajjad; Abdollahpour , Azam; Nasiri Farsani , Mokhtar (Mental Health and Lifestyle Journal, 2026)
Children with developmental disorders experience a constellation of motor, sensory, emotional, and social challenges that place them at heightened risk for physical inactivity, maladaptive lifestyle habits, and elevated psychological distress. Aquatic exercise has emerged as a promising intervention capable of addressing these interconnected difficulties through its unique biomechanical and sensory properties. This narrative review synthesizes recent evidence on the physiological, psychological, and behavioral effects of aquatic exercise programs, drawing from diverse studies involving vulnerable populations whose mechanisms of change parallel those seen in developmental disabilities. Findings reveal that aquatic environments support improvements in balance, motor coordination, muscular strength, and functional mobility, offering children with motor impairments a supportive medium for movement exploration. Psychological benefits include reductions in anxiety, stress, and emotional dysregulation, attributed to the calming sensory input and rhythmic proprioceptive feedback provided by water. Aquatic programs also foster health-promoting lifestyle behaviors by increasing motivation for physical activity, improving self-care routines, and enhancing stress management. Social engagement is strengthened through cooperative play and peer interaction, which occur more naturally in water-based settings. Despite these promising outcomes, the literature remains limited by heterogeneity in program structure, small sample sizes, and a scarcity of child-specific research. Nonetheless, the integrative benefits observed across physical, emotional, and behavioral domains highlight the value of aquatic exercise as a holistic therapeutic modality. This review emphasizes the potential of aquatic programs to support inclusive rehabilitation frameworks and underscores the need for more rigorous research focused on children with developmental disorders.